KEPEMIMPINAN DIGITAL DALAM DUNIA PENDIDIKAN: TINJAUAN SYSTEMATIC LITERATURE REVIEW - Fauzi, Farid (TA’LIM : Jurnal Studi Pendidikan Islam, 2025)
Abstract This article examines the role of digital leadership in education through the Systematic Literature Review (SLR) approach using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method. The main findings indicate that the readiness of human resources (HR) in implementing digital leadership at the education level is still limited. Many leaders and administrative staff do not yet have a deep understanding of digital transformation, which hinders the success of digital initiatives. Therefore, training and development programs that focus on technical and soft skills such as adaptive leadership and digital literacy are very important. In addition, effective digital leadership plays an important role in driving digital innovation, which increases the efficiency and competitiveness of educational institutions. A well-implemented digital culture allows for the integration of technology in learning and management, supporting collaboration and experimentation. Finally, digital transformation requires visionary leaders who are able to integrate technology with educational strategies, creating adaptive and innovative cultural changes in teaching. In conclusion, digital leadership plays a key role in accelerating sustainable educational transformation in the world of education through a digital culture of human resource development and digital innovation. Abstrak Artikel ini mengkaji peran kepemimpinan digital dalam dunia pendidikan melalui pendekatan Systematic Literature Review (SLR) dengan menggunakan metode PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Temuan utama menunjukkan bahwa kesiapan sumber daya manusia (SDM) dalam menerapkan kepemimpinan digital di tingkat pendidikan masih terbatas. Banyak pemimpin dan staf administrasi belum memiliki pemahaman yang mendalam mengenai transformasi digital, yang menghambat keberhasilan inisiatif digital. Oleh karena itu, pengembangan program pelatihan yang berfokus pada keterampilan teknis dan soft skills seperti kepemimpinan adaptif serta literasi digital menjadi sangat penting. Selain itu, kepemimpinan digital yang efektif berperan penting dalam mendorong inovasi digital, yang meningkatkan efisiensi dan daya saing institusi pendidikan. Budaya digital yang diterapkan dengan baik memungkinkan integrasi teknologi dalam pembelajaran dan manajemen, mendukung kolaborasi dan eksperimen. Terakhir, transformasi digital membutuhkan pemimpin yang visioner dan mampu mengintegrasikan teknologi dengan strategi pendidikan, menciptakan perubahan budaya yang adaptif dan inovatif dalam pengajaran. Kesimpulannya, kepemimpinan digital memainkan peran kunci dalam mempercepat transformasi pendidikan yang berkelanjutan pada dunia pendidikan melalui budaya digitalm pengembangan sumber daya manusia dan inovasi digital.